A Thorny Path $1 (BVolume 07s - Ebers, Georg, 1837-1898; Bell, Clara, 1834-1927 (Salt Lake City, UT : Project Gutenberg, 2004)
"A Thorny Path $1 (BVolume 7" by Georg Ebers is a historical novel written in the late 19th century. Set in ancient Rome and Alexandria, the story revolves around the young woman Melissa, who finds herself entangled in the dangerous web of imperial power and desire, particularly with the volatile Emperor Caracalla. As Melissa navigates the complexities of ambition, love, and loyalty, the narrative offers a vivid portrayal of the treacherous political landscape and the challenges faced by women in a patriarchal society. At the start of the story, we witness Melissa preparing for a meeting with Caesar, amidst the anxiety of her friends who fear for her safety due to the emperor's known temperament. She exudes an optimistic innocence, believing her humble lineage protects her from the emperor$1 (Bs unwanted advances. However, her beliefs are soon challenged as she faces the unwelcome attention of Caesar's bodyguards, leading to a confrontation with Caracalla himself. The opening chapters lay the groundwork for Melissa's internal struggle$1 (Bbetween her duty towards her family, her feelings for her betrothed Diodoros, and her attempts to maintain her dignity in the face of male aggression and imperial wrath. The complex dynamics of power, gender, and fate are deftly interwoven as the story unfolds, promising readers a captivating journey through a vivid historical setting. (This is an automatically generated summary.)s
Release date is 2004-04-01
This eBook was produced by David Widger
Keywords: Egypt -- History -- 30 B.C.-640 A.D. -- Fiction; German fiction -- Translations into English